1995
DOI: 10.1123/japa.3.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Exercise: A Prevention and Treatment for Osteoporosis and Injurious Falls in the Older Adult

Abstract: Osteoporosis is a major public health problem in persons over the age of 65, and it leads to approximately 250,000 hip fractures per year. Contributing risk factors for osteoporosis and hip fractures in the aging population include insufficient nutrient intake, inadequate dietary calcium, muscular weakness, decreased physical activity, and changes in hormonal homeostasis. Physical activity especially plays an important role in the prevention of falls and fractures. Physically active older adults with greater m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…This is in agreement with several observational (53,54) and intervention studies. This is in agreement with several observational (53,54) and intervention studies.…”
Section: Associations Between Determinants With Total Hip Bmdsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with several observational (53,54) and intervention studies. This is in agreement with several observational (53,54) and intervention studies.…”
Section: Associations Between Determinants With Total Hip Bmdsupporting
confidence: 93%
“…We found a protective effect of physical activity on total hip BMD in men and women. This is in agreement with several observational (53,54) and intervention studies. (8,9,55) Men who were current smokers had lower total hip BMD, which agrees with the results of prior studies.…”
Section: Associations Between Determinants With Total Hip Bmdsupporting
confidence: 93%
See 1 more Smart Citation
“…Several such studies can be found in the literature 8 . These have been largely restricted to healthy postmenopausal women who present no risk factor for osteoporosis 9 . To our knowledge, no randomized controlled trial has ever been conducted to estimate the effectiveness of physical activity in women with bone mass below a preset threshold.…”
mentioning
confidence: 99%
“…It has been estimated that at least 90% of hip fractures result from a fall [10], and there is evidence that fall-related risk factors such as impaired lower limb strength, postural sway, reaction time and walking speed are also risk factors for hip fracture [11]. There is also evidence that muscle strength [12], postural sway and walking speed [13] are further impaired following hip fracture.…”
Section: Introductionmentioning
confidence: 99%